ANALISIS PENERAPAN COST OF QUALITY UNTUK MENINGKATKAN KUALITAS PRODUK PADA PERUSAHAAN HUMBLE PROJECT TASIKMALAYA - Febi, Aceng (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Quality products can be achieved by the company must always monitor and improve the quality of its products. Costs incurred in relation to efforts to improve product quality are called quality costs. The purpose of this study was to determine the application of the cost of quality or the cost of quality to improve product quality. This research was conducted at the Humble Project, which is a company engaged in the clothing industry. The method used by the author is descriptive qualitative method. The data sources used are primary and secondary data sources. The data collection technique uses purposive sampling. The results of the study show that from the components taken, it can be concluded that the Humble Project has implemented quality costs but needs to maximize the Cost of Quality or Quality Costs in the business being carried out